Toward e-business: factors linking information technology adoption in Malaysian software firms - Mohamed, Norshidah; Hussein, Ramlah; Ahlan, Abdul Rahman; Hazza, Zubaidah Muataz (The International Academy of E-Business, 2010)
This paper seeks to identify factors that link information technology adoption in Malaysian software firms. Our research model is an adaptation of Thong (1999) that identified Chief Executive Officers characteristics; and Tornatzky and Fleischer (1990)that identified technological, organizational and environmental contexts as influencing factors in the process by which an organization adopts, implements end users technological innovation. We conducted a survey research in Malaysia to test our research framework. Using correlation and t-test analyses, we found the evidence for the link between the age of firm, firms' research and development focus, availability of government financial assistance and adoption of information technology in Malaysian software firms.